AB0883 SYSTEMIC INFLAMMATION AND ATHEROSCLEROSIS IN PATIENTS WITH GOUT. RESULTS FROM THE NOR-GOUT STUDY. (June 2019) - Rollefstad, Silvia; Uhlig, Till; Karoliussen, Lars Fridtjof; Hammer, Hilde Berner; Semb, Anne Grete
Abstract : Background: The association between gout and cardiovascular disease (CVD) is well known, 1 whereas mechanisms behind this association are poorly understood. Objectives: This study aimed to evaluate factors associated with asymptomatic carotid atherosclerosis in patients with gout. Methods: In this prospective study patients with crystal-proven gout were included after a recent disease flare, if the serum urate level was >360 μmol/L (>6 mg/dl). We analysed baseline data in patients without established CVD who were referred to a CVD risk evaluation, including ultrasound of the carotid arteries, blood pressure measurement and laboratory tests. Carotid atherosclerotic plaques were defined in the longitudinal view as protrusions into the lumen of ≥1.5 mm or at least 2 times the adjacent intima-media thickness according to the Mannheim criteria. Results: Of the 79 gout patients included, approximately 10% were females, and mean (SD) age was 52.1±13.1 years. Thirty-two (40.5%) had carotid plaques (Table). Only 9.3% were current smokers, while mean (SD) body mass index was high (29.1±4.7 kg/m 2 ). Lipids were in the normal range, with a mean (SD) total cholesterol at 5.3±1.09 mmol/L and low density lipoprotein cholesterol 3.12±0.95 mmol/L. Systolic blood pressure was in the normal range 134.0±15.1 mmHg, although 29.1% of the patients were treated with antihypertensive agents. In univariate analyses, higher age, hypertension and higher erythrocyte sedimentation rate (as a marker of systemic inflammation) were significantly associated with the presence of carotid plaques (p=0.01 and p=0.04, respectively) (Figure). Serum urate levels or disease duration were not associated with carotid plaques (p=0.27 and p=0.44, respectively). Conclusion: Our results indicate an association between systemic inflammation and atherosclerosis in patients with gout. To be able to efficiently prevent CVD in this patient group, prospective studies with larger sample sizes are needed to elucidate the mechanisms behind the increased risk of CVD in gout patients. References: [1] Choi HK, Curhan G. Independent impact of gout on mortality and risk of coronary heart disease. Circulation2007;116:894-900. Disclosure of Interests: Silvia Rollefstad: None declared, Till Uhlig Consultant for: Grünenthal, Novartis, Speakers bureau: Grünenthal, Novartis, Lars Fridtjof Karoliussen: None declared, Hilde Berner Hammer Grant/research support from: AbbVie, Pfizer and Roche, Paid instructor for: AbbVie, Pfizer, UCB, Novartis, Roche, Speakers bureau: AbbVie, Pfizer, UCB, Novartis, Roche, Anne Grete Semb: None declared